Designing Practical Guides Based on Simple Tools and Materials to Improve Students' Understanding in Scientific Learning at School - Tampi, Grichelle; Nanlohy, Fanny Nella; Posumah, Dany (Lembaga Penelitian dan Pendidikan Mandala, 2024)
Scientific learning plays an important role in the development of students' understanding of concepts and skills in science. Although there are often obstacles in providing practical experience to students, this triggers teacher creativity and innovation to overcome the limitations of tools and materials at school. This study aims to design a practicum guide based on simple tools and materials that are feasible to use to improve student understanding in scientific learning at school. The research method used in this study is the development research method according to Borg and Gall (1983) modified by Rengkuan and Howan (2016), into five development steps which include: (1) Need Analysis & Reference Study, (2) Material Development, (3) Expert Validation, (4) Try Out, (5) Final Production. The results showed the feasibility of designing a practicum guide based on simple tools and materials obtained from material experts with a percentage of 93.3% with a very feasible category, from media experts with a percentage of 90.3% with a very feasible category, from student practicality assessments with a percentage of 84.3% with a very feasible category, and from teacher responses with a percentage of 90.3% with a very feasible category. So it can be concluded that the design of practicum guides based on simple tools and materials is very feasible to use to improve student understanding in scientific learning at school. <